International Handbook of Survey Methodology (L. Erlbaum Associates, 2008)
Taking into account both traditional and emerging modes, this comprehensive new Handbook covers all major methodological and statistical issues in designing and analyzing surveys. With contributions from the world's leading survey methodologists and statisticians, this invaluable new resource provides guidance on collecting survey data and creating meaningful results. Featuring examples from a variety of countries, the book reviews such things as how to deal with sample designs, write survey questions, and collect data on the Internet. A thorough review of the procedures associated with multiple modes of collecting sample survey information and applying that combination of methods that fit the situation best is included.